Effects of Dew Removal and Mowing Frequency on Fungicide Performance for Dollar Spot Control - Delvalle, Tanner C (Plant disease, 2011)
Dollar spot (Sclerotinia homoeocarpa) is a severe disease problem on creeping bentgrass (Agrostis stolonifera) fairways. The objective of this study was to evaluate the effects of dew removal and mowing frequency on fungicide performance for dollar spot control. In 2009 and 2010, an experiment involving daily dew removal or no dew removal, mowing frequency (2, 4, and 6 days week-1), and fungicides (chlorothalonil, propiconazole, and iprodione) was conducted on creeping bentgrass maintained as a fairway. Daily dew removal resulted in fewer dollar spot infection centers (IC) compared with not removing dew during late summer 2009 and 2010 for all mowing-frequency and fungicide treatments. As mowing frequency increased from 2 to 6 days week-1, dollar spot IC decreased when averaged across all fungicide treatments. For all fungicides, daily dew removal increased the number of days needed to reach a 15-IC plot-1 point of reference when compared with fungicide treatments in which dew was not removed. The number of days required to reach 15 IC varied with fungicide, mowing frequency, and year the test was conducted. Results demonstrate that dollar spot control with fungicides can be extended when daily dew removal is employed and, in some cases, when mowing frequency is increased on dew-covered turf. Benefits of dew-removal practices on dollar spot and fungicide performance can vary with weather conditions, fungicide, threshold level, and possibly other factors